Psychosocial adjustment to sex reassignment surgery: a qualitative examination and personal experiences of six transsexual persons in Croatia - Jokić-Begić, Nataša (Array, 2014)
In Croatia, transgender individuals face numerous social and medical obstacles throughout the process of transition. The aim of this study was to depict the factors contributing to the psychosocial adjustment of six transsexual individuals living in Croatia following sex reassignment surgery (SRS). A combination of quantitative and qualitative self-report methods was used. Due to the specificity of the sample, the data were collected online. Standardized questionnaires were used to assess mental health and quality of life alongside a series of open- ended questions divided into 4 themes: the decision-making process regarding SRS ; social and medical support during the SRS process ; experience of discrimination and stigmatizing behaviors ; psychosocial adjustment after SRS. Despite the unfavorable circumstances in Croatian society, participants demonstrated stable mental, social, and professional functioning, as well as a relative resilience to minority stress. Results also reveal the role of pretransition factors such as high socioeconomic status, good premorbid functioning, and high motivation for SRS in successful psychosocial adjustment. During and after transition, participants reported experiencing good social support and satisfaction with the surgical treatment and outcomes. Any difficulties reported by participants are related to either sexual relationships or internalized transphobia. The results also demonstrate the potentially protective role that a lengthier process of transition plays in countries such as Croatia.